Mars, Incorporated : Skittles becomes part of a controversial shooting - Boylan, Matthew, (SAGE Knowledge. Cases., 2017)
In 2012, a shooting in Florida rose to national prominence after it was revealed that no charges would be pressed against the 28-year-old man who shot and killed an unarmed teenager who was carrying a bag of Skittles candies at the time of his death. The brand became a central symbol of the controversy as discussions about the shooting grew on social media and protests arose throughout the country.